Acute pericardial effusion representing the TNF-α-mediated severe inflammation but not the coronary artery outcome of Kawasaki disease. (May 2015) - Okada, S; Hasegawa, S; Suzuki, Y; Matsubara, T; Shimomura, M; Okuda, M; Ichiyama, T; Ohga, S
<x xml:space="preserve">Abstract</x> Objectives: To establish the optimal inflammation control of Kawasaki disease (KD), we investigated the clinical and pathophysiological basis of pericardial effusion (PE) during the acute phase of KD. Method: Clinical and laboratory features of Japanese KD children with PE (PE group: n = 9) and without PE (non-PE group: n = 89) were studied retrospectively by using the medical records. Serum levels of soluble tumour necrosis factor receptor 1 (sTNFR1), interleukin 6 (IL-6), and vascular endothelial growth factor (VEGF) were assessed by enzyme-linked immunosorbent assays (ELISAs). Results: PE group patients had coronary artery lesions (CALs) more frequently than non-PE group patients during the acute phase of KD (33% vs. 5.6%, p = 0.024). PE patients also showed lower levels of haemoglobin (p < 0.01) and serum albumin (p < 0.01) and higher platelet counts (p = 0.013) than non-PE patients. The proportion of neurological symptoms, but not other manifestations, in the PE group was higher than in the non-PE group (p = 0.022). All patients survived free from coronary artery aneurisms. Serum levels of sTNFR1, but not the other cytokines, in the PE group were higher than those in the non-PE group (p < 0.001). The sTNFR1 levels correlated positively with C-reactive protein (CRP) (r = 0.30, p = 0.019) or total bilirubin (r = 0.40, p < 0.01) levels. Conclusions: Acute PE in KD patients indicated the severity of TNF-mediated vascular inflammation and concurrent CALs. According to the progression, these patients might need more targeted therapy of anti-inflammation for a better coronary outcome.